Dampak Migrasi TKW terhadap Pengasuhan Keluarga di Indramayu: Peran Remitan dalam Menyokong Kesejahteraan - Ahmad Ro’i Alfaza; Bambang Yuniarto; Ahmad Sururi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The migration of Indonesian Women Workers (TKW) significantly contributes to family economies through remittances but also creates social and emotional challenges. This study aims to analyze the impact of TKW migration on child-rearing patterns and the role of local communities in supporting their families in Indramayu. A qualitative approach using a case study method was employed, involving in-depth interviews, observations, and document analysis. The results reveal that remittances from TKW serve as the primary source of family income, yet the absence of mothers causes emotional gaps and changes in parenting patterns. Children are often cared for by grandparents or placed in Islamic boarding schools (pesantren), leading to varied effects on their education and discipline. Faith-based communities play a significant role in supporting TKW families, particularly through moral and social education. This study recommends strengthening the role of local communities and implementing social protection policies for TKW and their families to mitigate the negative impacts of migration.